Resisting Hegemonic Discourses on the Relation Between Teaching Second Languages and Socioeconomic Development - Ferney Cruz-Arcila; Vanessa Solano-Cohen; María Liliana Briceño-González; Ana Rincón; Antonio Lobato-Junior (Profile: Issues in Teachers' Professional Development)
This study examines hegemonic discourses on English and socioeconomic development from teachers’ perspectives. Specifically, it scrutinizes the sorts of positions a group of 36 teachers of English, French, Italian, German, and Portuguese in an undergraduate program of modern languages take towards both the predominant narrative of English as the language of development and the role that the languages they teach may also play. Using postdevelopment as a theoretical framework, teachers’ social representations around the languages they teach are analyzed. Findings suggest that, although there is a strong tendency to uncritically accept and accommodate instrumental and Anglo normative views of development, “small hopes” for configuring plural, locally sensitive, less instrumental, and ecological understandings are also emerging.